Profitability-Liquidity Tradeoff : The Evidence on Malaysian Listed Companies - Maziah, Sarnua (2005)
This study attempts to examine the determinant of companies' profitability in Malaysia. This study used the net operating income to measure profitability of company; current ratio and cash gap are used to measure liquidity and sales are used to measure the size of company. The sample of this study comprise of 166 companies listed on the Main Board of Bursa Malaysia covering period of 1998 to 2003. Overall, the regression models showed that the current ratio (CR) is consistently positive and significant with net operating income (NOI). However, the negatively significant relationship is found between profitability and liquidity as measures by cash gap (cash conversion cycle). This study finds that CR is the most important liquidity measure that affects profitability. This study has observed the relationship between size and profitability of company. Size is also found to bear some influence over profitability. Therefore, the regression model showed that Malaysian companies have a positive relationship between NOI and size. Finally, this study suggests that size, current ratio and cash gap are significant determinants of the variability of profitability.